2013
DOI: 10.1051/0004-6361/201220652
|View full text |Cite
|
Sign up to set email alerts
|

The average GeV-band emission from gamma-ray bursts

Abstract: Aims. We analyze the emission in the 0.3-30 GeV energy range of gamma-ray bursts detected with the Fermi Gamma-ray Space Telescope. We concentrate on bursts that were previously only detected with the Gamma-Ray Burst Monitor in the keV energy range. These bursts will then be compared to the bursts that were individually detected with the Large Area Telescope at higher energies. Methods. To estimate the emission of faint GRBs we used nonstandard analysis methods and sum over many GRBs to find an average signal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
4
2
0
Order By: Relevance
“…Our detection of ubiquitous long-lived emission, albeit below the LAT detection threshold, is consistent with similar work performed by Lange & Pohl (2013). In their work, the authors examined a sample of 99 GBM localized GRBs that were not detected by LAT and found evidence for long-lived subthreshold emission that lasted for as much as 10 times the bursts' T 90 duration in the keV-MeV energy range.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our detection of ubiquitous long-lived emission, albeit below the LAT detection threshold, is consistent with similar work performed by Lange & Pohl (2013). In their work, the authors examined a sample of 99 GBM localized GRBs that were not detected by LAT and found evidence for long-lived subthreshold emission that lasted for as much as 10 times the bursts' T 90 duration in the keV-MeV energy range.…”
Section: Discussionsupporting
confidence: 90%
“…In their work, the authors examined a sample of 99 GBM localized GRBs that were not detected by LAT and found evidence for long-lived subthreshold emission that lasted for as much as 10 times the bursts' T 90 duration in the keV-MeV energy range. Unlike the conclusions drawn by Lange & Pohl (2013), though, we find that the photon index of the subthreshold population derived from our joint likelihood analysis is largely consistent with that observed in the LAT-detected bursts. The different results may be due to the different techniques employed, with the hardest bursts in our sample contributing most significantly to the joint likelihood results, and hence possibly providing a harder average photon index than that measured by Lange & Pohl (2013).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Several observations are related to the temporal variations of spectra. This way, the spectral lags were found between different low energy bands [5] and the very-high-energy radiation was discovered to be extended relative to the x-ray emission [6,7,1]. In this paper we go further and compare the temporal extension of GRB gamma-ray radiation in the two energy bands 100 MeV < E < 1 GeV and E > 1 GeV (hereafter, low and high-energy bands) using the data from the Large Area Telescope (LAT) of the Fermi satellite [8,9].…”
Section: Introductionmentioning
confidence: 95%